Pengaruh Fasilitas Kerja dan Kompetensi terhadap Motivasi Kerja yang Berimplikasi pada Kinerja Pegawai di PT. Bank Tabungan Negara (PERSERO) Tbk Cabang Jambi - Waode Apria Dega Gaputri; M. Zahari MS; Osrita Hapsara (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study is to obtain an overview of work facilities, competencies, work motivation, and employee performance at PT. State Savings Bank (Persero) Tbk Jambi Branch. To determine the direct and indirect effects of work facilities and competence on employee motivation at PT. State Savings Bank (Persero) Tbk Jambi Branch. To determine the direct and indirect effects of work facilities and competence on employee performance at PT. State Savings Bank (Persero) Tbk Jambi Branch. To determine the effect of work motivation on employee performance at PT. State Savings Bank (Persero) Tbk Jambi Branch. To determine the effect of work facilities and competence through work motivation on employee performance. The type of data obtained in this study uses quantitative data sourced from primary data obtained by conducting research and questionnaires, secondary data can be obtained by reading, studying and understanding through other media sourced from literature and library books or data from companies related to the research. In this research, the object of research is employees of PT. State Savings Bank (Persero) Tbk Jambi Branch. Work Facilities and Competence simultaneously affect the motivation of employees of PT. State Savings Bank (Persero) Tbk Jambi Branch. Work Facilities and Competence partially have a positive and significant impact on Motivation. Work Facilities and Competence simultaneously have a significant effect on the performance of employees of PT. State Savings Bank (Persero) Tbk Jambi Branch. Work Facilities and Competence partially have a significant effect on performance. Motivation has a significant effect on employee performance at PT. State Savings Bank (Persero) Tbk Jambi Branch. The suggestions put forward should be for the leader to play an active role by providing special attention accompanied by rewards so that the work process undertaken gives good results.